USE OF INTERACTIVE FORMS AND METHODS IN LEARNING (American Journal of Business Management, Economics and Banking, 2022)
The peculiarities of the interactive forms and methods in teaching medical University and institute biophysics are touched upon in the article as the most modern and innovative. Some examples of the forms are shown in the article for practical usage in teaching.